Exploration of Emerging Trends and Paradigms in Leadership and Governance Research and Practice in Thailand - Kittichat, Chakan (International Journal of Leadership and Governance, 2024)
Purpose: The aim of the study was to investigate the exploration of emerging trends and paradigms in leadership and governance research and practice Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Emerging trends in Thai leadership and governance highlight a shift towards inclusive decision-making, ethical frameworks, and digital engagement. Sustainability and environmental stewardship are gaining importance, reflecting global concerns. This dynamic landscape blends traditional values with evolving practices. Unique Contribution to Theory, Practice and Policy: Transformational leadership theory, complexity leadership theory & adaptive governance theory may be used to anchor future studies on the exploration of emerging trends and paradigms in leadership and governance research and practice. Implementing leadership development programs based on evidence-based practices and theories of effective leadership Developing policies to enhance transparency and accountability in government institutions, such as open data initiatives or whistleblower protection laws.